Adaptive genetic algorithm enabled tailoring of piezoelectric metamaterials for optimal vibration attenuation - Jian, Yupei (2022)
Piezoelectric metamaterials with shunt resonant circuits have been extensively investigated for their tunability in bandgaps. However, the vibration attenuation ability induced by the electromechanical coupling is generally weaker than that of mechanical metamaterials, limiting their applications in engineering practice. This research presents a non-uniform piezoelectric metamaterial beam with shunt circuit parameters optimized by an adaptive genetic algorithm (AGA) for tailoring the vibration attenuation zone. First, the non-uniform piezoelectric metamaterial beam is modeled for transmittance analysis and verified by the finite element method. By simultaneously tuning the resonance frequencies and the resistance of the shunt circuits, it is conceptually demonstrated that the attenuation zone can be broadened, and the undesired localized vibration modes can be mitigated. Subsequently, two optimization strategies are proposed respectively for two typical vibration scenarios. The inductances and the load resistance in the shunt circuits constitute the set of design variables and are optimized by the AGA. Dedicated case studies are carried out, and the results show that the objective-oriented circuitry parameters can greatly enrich the design freedom, and tailor the transmittance profile according to a given vibration spectra. As compared to the conventional uniform and the graded piezoelectric metamaterial beams, the proposed design provides superior vibration attenuation performance and demonstrates a promising approach for tailoring piezoelectric metamaterials systems.